A nonrandom walk down Hollywood boulevard: Celebrity deaths and investor sentiment. Issue 3 (29th October 2020) - Lepori, Gabriele M.
Abstract: Motivated by psychological evidence that shows the public experiences emotional distress in response to the deaths of popular figures, I employ the deaths of 1, 391 Hollywood Walk of Fame celebrities as natural experiments to identify exogenous public mood changes over the period 1926–2009. Consistent with the psychological theories which maintain that sadness encourages individuals to favor high‐risk/high‐reward investments, I find that U.S. stock returns are abnormally high immediately after the death of a major celebrity. This effect is particularly large during periods of high market‐level uncertainty (+0.40%) and for stocks headquartered in the city where the celebrity died (+0.26%).